Assessing driving‐relevant attentional impairment after a multiday drinking session: A two‐phase pilot study. (11th April 2022) - Norman, Thomas; Monds, Lauren A.; Dilevski, Natali; Riordan, Benjamin; Peacock, Amy; Ferguson, Stuart G; Kuntsche, Emmanuel; Bruno, Raimondo
Abstract: Background: The possibility of residual impairment of cognitive performance after multiday drinking sessions is particularly important given the potential for the deleterious effects of fatigue and hangover. This pilot study aimed to devise a methodology to compare sober performance on driving‐relevant attentional tasks at the end of a 4‐day music festival with performance at varying levels of the breath–alcohol curve. Methods: Fifty‐two participants completed selective and sustained attention tasks at a breath alcohol concentration (BrAC) of 0.00%, 0.05%, and 0.08% following acute dosing in a controlled laboratory setting. A subset of participants ( n = 13) were then tested at the conclusion of a 4‐day music festival at 0.00% BrAC, with task performance compared with laboratory results. Results: During the laboratory phase, sustained attention was poorer at the 0.05% ascending timepoint only (compared to 0.00% BrAC). During the festival phase, participants made a greater number of errors on the selective attention task predeparture than at 0.00% and 0.05% BrAC in the laboratory. Sustained attention performance was poorer while intoxicated in the laboratory. Conclusions: Our findings suggest that the absence of blood alcohol acutely may not be indicative of unimpaired cognitive performance and that other factors related to multiday drinking may produce driving‐related attentional deficits. The findings reinforce the need to measure attentional performance in real‐world drinking contexts despite the methodological complexities of doing so. A larger study is warranted to replicate the findings and should include attentional measures that either are more sensitive to the effects of acute alcohol intoxication than those in our study or are based on a driving simulator. Abstract : Beyond acute alcohol intoxication, fatigue and hangover are factors of concern for individuals planning to drive after a drinking session. In this two‐phase pilot study, we devise a methodology to assess driving‐relevant attentional performance in both a controlled (i.e., laboratory) and naturalistic drinking (i.e., music festival) setting, comparing the two. A reduction in attentional performance was seen in participants following engagement in the naturalistic setting, signalling a need to more closely evaluate the deleterious effect of these environments on attention.